Strengthening MSME Competitiveness Through Integrated Digital Marketing Literacy: A Community-Based Training Intervention - Susanto Pranoto, Henry; Kurniawan, Daniel; Nainggolan, Romauli; Wijayadne, Devi Rahnjen (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) often prioritize short-term sales activities while paying limited attention to strategic business management, thereby constraining their long-term sustainability and growth. To address this challenge, a Community Service Program (PKM) was implemented for 108 MSME practitioners from the GBI House of Grace congregation under the theme, “Don’t Just Sell, Learn Smart Ways to Manage Your Business.” The program aimed to enhance participants’ understanding of fundamental business management concepts and strengthen their capacity for strategic planning. The intervention adopted the Planning–Implementation–Evaluation (PIE) framework and employed the Business Model Canvas (BMC) as the primary learning tool. To facilitate participant engagement and reduce the complexity of business planning, the training incorporated a visual mapping approach using adhesive notes (Post-Its) to identify and organize key business components. Activities included interactive lectures, group discussions, guided mentoring, and practical BMC workshops. Observational findings revealed that participants were able to identify customer segments, value propositions, key partnerships, revenue streams, and cost structures more systematically. The success of the program was further supported by a strong community-based learning environment and an intensive mentoring model involving three faculty members and twenty-six university students. The program demonstrates that visual and participatory business management training can effectively improve entrepreneurial awareness and strategic thinking among grassroots MSMEs. These findings highlight the importance of community-centered capacity-building initiatives in strengthening the sustainability and competitiveness of MSMEs.Usaha Mikro, Kecil, dan Menengah (UMKM) sering kali lebih berfokus pada aktivitas penjualan jangka pendek dibandingkan pengelolaan bisnis yang bersifat strategis, sehingga membatasi keberlanjutan dan pertumbuhan usaha dalam jangka panjang. Untuk menjawab tantangan tersebut, dilaksanakan Program Pengabdian kepada Masyarakat (PKM) yang melibatkan 108 pelaku UMKM dari jemaat GBI House of Grace dengan tema “Jangan Sekadar Jualan, Pelajari Cara Cerdas Mengelola Usahamu.” Program ini bertujuan meningkatkan pemahaman peserta mengenai konsep dasar manajemen bisnis serta memperkuat kemampuan perencanaan strategis usaha. Kegiatan dilaksanakan menggunakan kerangka Planning–Implementation–Evaluation (PIE) dan memanfaatkan Business Model Canvas (BMC) sebagai media pembelajaran utama. Untuk meningkatkan keterlibatan peserta dan mengurangi kompleksitas perencanaan bisnis, pelatihan menerapkan pendekatan pemetaan visual menggunakan kertas tempel (Post-It) dalam mengidentifikasi dan mengorganisasi komponen-komponen utama bisnis. Kegiatan mencakup penyampaian materi, diskusi interaktif, pendampingan, serta praktik penyusunan BMC. Hasil observasi menunjukkan bahwa peserta mampu mengidentifikasi segmen pelanggan, proposisi nilai, kemitraan utama, sumber pendapatan, dan struktur biaya secara lebih sistematis. Keberhasilan program juga didukung oleh lingkungan pembelajaran berbasis komunitas yang kuat serta model pendampingan intensif yang melibatkan tiga dosen dan dua puluh enam mahasiswa. Program ini menunjukkan bahwa pelatihan manajemen bisnis yang bersifat visual dan partisipatif efektif dalam meningkatkan kesadaran kewirausahaan dan kemampuan berpikir strategis pelaku UMKM akar rumput. Temuan ini menegaskan pentingnya inisiatif penguatan kapasitas berbasis komunitas untuk mendukung keberlanjutan dan daya saing UMKM.